BDNF mediates the protective effects of scopolamine in reserpine-induced depression-like behaviors via up-regulation of 5-HTT and TPH1. (January 2019) - Yu, Hanjie; Lv, Dan; Shen, Mengxin; Zhang, Yanhua; Zhou, Dongsheng; Chen, Zhongming; Wang, Chuang
Highlights: Chronic reserpine treatment induced the significant depression-like behaviors in mice. Scopolamine significantly ameliorated the behavioral dysfunctions in the FST of mice. The down-regulation of 5-HTT, TPH1and BDNF in the hippocampus and PFC induced by reserpine were significantly reversed by scopolamine in mice. The antidepressant-like effects of scopolamine is mediated, at least in part, via modulating the 5-HTT, TPH1and BDNF in the hippocampus and PFC. Abstract: Reserpine treatment in rodents has been shown to induce depression-like behaviors that mimic monoamine dysfunction implicated in the development of depression. Herein, we aimed to demonstrate the antidepressant-like activities of scopolamine, the muscarinic receptor antagonist, in a reserpine-induced mouse model. Mice were injected with 1.5 mg/kg (i.p.) of reserpine for 10 days, and the depression-like state was confirmed via the open field test (OFT) and forced swimming test (FST). Then, the mice were treated with scopolamine (25 µg/kg, i.p.) or saline for 3 days. Ten days of reserpine treatment resulted in a significant decrease in locomotor activity and an increase in immobility time in the OFT and FST, respectively, indicating that ten days of reserpine administration significantly induced depression-like behaviors in mice. However, scopolamine rapidly ameliorated the increase in immobility time in the FST and had no effect on locomotor activity in the OFT. In addition, the reserpine-induced decreases in serotonin transporter (5-HTT), brain-derived neurotrophic factor (BDNF) and tryptophan hydroxylase 1 (TPH1) in mouse hippocampus and prefrontal cortex (PFC) were significantly reversed by scopolamine. Our study provides evidence that scopolamine rapidly attenuates reserpine-induced depression in mice partially by regulating 5-HTT, BDNF and TPH1 in the hippocampus and PFC of mice.